2022
DOI: 10.1007/s11356-022-23664-8
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed CZTS thin films and its simulation study for solar cell applications with ZnTe as the buffer layer

Abstract: The use of ZnTe as the buffer layer in the Cu 2 ZnSnS 4 (CZTS) based solar cells showed the improvement in overall e ciency. It may also reduce the overall cost of these cells as both the layers (absorbing and buffer) are having eco-friendly and earth abundant constitutes. The sol-gel spin coating method is used for the deposition of CZTS thin lms on the corning glass substrates. The X-ray diffraction studies showed the peaks corresponding to (112), ( 200), ( 220) and ( 312) planes which con rmed the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although there is currently a significant efficiency difference between CZTS and CIGS, numerous groups are conducting extensive research to look for strategies to enhance CZTS performance [17,18]. A significant challenge for CIGS and CZTS technology in the future price reductions are planned while increasing the productivity of related cells, particularly by swapping out the hazardous CdS buffer layer material for a less effective Cd-free buffer [19] CIGS-based cell attempts have shown the usefulness of a number of materials, particularly zinc sulphur (ZnS), having high conversion rates that are similar to the CdS layer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is currently a significant efficiency difference between CZTS and CIGS, numerous groups are conducting extensive research to look for strategies to enhance CZTS performance [17,18]. A significant challenge for CIGS and CZTS technology in the future price reductions are planned while increasing the productivity of related cells, particularly by swapping out the hazardous CdS buffer layer material for a less effective Cd-free buffer [19] CIGS-based cell attempts have shown the usefulness of a number of materials, particularly zinc sulphur (ZnS), having high conversion rates that are similar to the CdS layer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Various works have been reported that show that CZTS is the best material for thin-film SCs. It has been observed that the CZTS-based SC with zinc telluride (ZnTe) as a buffer layer revealed an impressive power conversion efficiency (PCE) of 23.47% with the SC structure Mo/CZTS/ZnTe/ZnO/ZnO:Al 17 . In another study, TiO 2 was used as ETL, and the tin perovskite CH 3 NH 3 SnI 3 (MASnI 3 ) acted as an absorber layer (FTO/TiO 2 /CH 3 NH 3 SnI 3 /CZTS/Au).…”
Section: Introductionmentioning
confidence: 99%